Vtc5, a Novel Subunit of the Vacuolar Transporter Chaperone Complex, Regulates Polyphosphate Synthesis and Phosphate Homeostasis in Yeast - Desfougères, Yann (J Biol Chem, 2016)
SPX domains control phosphate homeostasis in eukaryotes. Ten genes in yeast encode SPX-containing proteins, among which YDR089W is the only one of unknown function. Here, we show that YDR089W encodes a novel subunit of the vacuole transporter chaperone (VTC) complex that produces inorganic polyphosphate (polyP). The polyP synthesis transfers inorganic phosphate (P(i)) from the cytosol into the acidocalcisome- and lysosome-related vacuoles of yeast, where it can be released again. It was therefore proposed for buffer changes in cytosolic P(i) concentration (Thomas, M. R., and O'Shea, E. K. (2005) Proc. Natl. Acad. Sci. U.S.A. 102, 9565–9570). Vtc5 physically interacts with the VTC complex and accelerates the accumulation of polyP synthesized by it. Deletion of VTC5 reduces polyP accumulation in vivo and in vitro. Its overexpression hyperactivates polyP production and triggers the phosphate starvation response via the PHO pathway. Because this Vtc5-induced starvation response can be reverted by shutting down polyP synthesis genetically or pharmacologically, we propose that polyP synthesis rather than Vtc5 itself is a regulator of the PHO pathway. Our observations suggest that polyP synthesis not only serves to establish a buffer for transient drops in cytosolic P(i) levels but that it can actively decrease or increase the steady state of cytosolic P(i).